The Influence of the COVID-19 Event on Deviant Workplace Behavior Taking Tianjin, Beijing and Hebei as an Example - Liu, Yingyan (Int J Environ Res Public Health, 2020)
Background: Since the beginning of 2020, the Corona Virus Disease has broken out globally. This public health incident has had a great impact on the work and life of the public. Aim: Based on the event system theory, this article explored the influence of the “COVID-19” event on emotional exhaustion and deviant workplace behaviors. Methods: This survey’s objects are employees working in Tianjin, Beijing, Hebei affected by the epidemic. Using the questionnaire star, the online platform of the Marketing Research Office of Peking University and “snowball” methods 700 questionnaires were collected. Results: The response rate was 89.71% (n = 700). Female employees are more sensitive to the perceived event strength of the novel coronavirus pneumonia than male employees (F = 10.94, p <0.001); Employees aged 30–40 affected by the epidemic have the highest level of emotional exhaustion (F = 5.22, p < 0.01); A higher education level leads to a higher level of emotional exhaustion (F = 4.74, p < 0.01); The emotional exhaustion is polarized with the annual family income (F = 4.099, p < 0.01). Conclusions: The novelty, disruption, criticality of the Corona Virus Disease event has had a positive impact on the emotional exhaustion of employees in the workplace; Emotional exhaustion plays a partly mediating role between event strength with constructive deviant behaviors, and destructive deviant behaviors. Emotional exhaustion has a positive effect on creative constructive deviant behaviors, challenging constructive deviant behaviors, and interpersonal destructive deviant behaviors. Emotional exhaustion has a negative impact on organizational destructive deviant behaviors, and has no significant impact on interpersonal constructive deviant behaviors.